PERTANGGUNGJAWABAN HUKUM TERKAIT PENGELOLAAN LIMBAH B3 DALAM FASILITAS KESEHATAN - Franky Yusuf (JOURNAL IURIS SCIENTIA, 2024)
The aim of this paper is to see how corporate criminal liability is realized in the form of hospitals and/or emergency hospitals in connection with criminal acts of disposal of solid medical waste during the Covid-19 pandemic, and to determine the factors that influence this criminal liability. The conclusion ob- tained is that companies and administrative officials who give orders to com- mit criminal acts can be held criminally responsible. Several factors can in- fluence the realization of criminal liability, namely less than optimal supervi- sion by law enforcement officials, unclear provisions, especially those related to emergency hospital accommodation, which requires legislative updates.